ALAT PENGISI BATERAI TELEPON SELULER BERBASIS ENERGI MATAHARI - Faridah Faridah; Rismawan Rismawan; Balza Achmad (Universitas Ahmad Dahlan, 2006)
Cellular phone battery recharging using conventional energy source, i.e. electricity supply, has disadvantage within the areas that are not covered by electricity grids (PLN). This research designed a prototype of cellular phone battery charger based on solar energy. Some solar cells were used to convert solar energy into electricity currents that fluctuated due to variation of sun light with 10.11 volt maximum voltage. Reserved batteries were used for temporary storage of the generated currents. Boost converter was used to stable the output voltage about 8 volt with input above 3 volt. The test showed that there was a variation on nominal voltage increase of the phone battery. At sunny condition and while the reserve battery was fully charged, Nokia N3350 battery voltage increased to 0.03 Volt in 30 minutes. For Siemens C45 battery recharging, the system must be reconfigured. The reconfigured system increased nominal battery voltage of 0.2 Volt in 2 hours.